Feline intervertebral disc disease: a review of the literature - Rayward, R. M. (Veterinary and Comparative Orthopaedics and Traumatology, 2002)
Intervertebral disc disease should be considered in the differential diagnosis of feline myelopathy. Animals of any age, breed or gender may be affected and onset of neurological dysfunction may be variable. The thoracolumbar junction and to a lesser extent the mid lumbar spine are the most commonly affected sites and Hansen type I disc extrusions predominate. Standard investigations (radiography, myelography, computed tomography, magnetic resonance imaging) and surgical techniques (laminectomy, hemilaminectomy, fenestration, durotomy) may be employed. Although response to conservative treatment is variable, surgically treated cases generally respond favourably but neurological recovery may be incomplete. Following surgical intervention, a recurrence of clinically significant IVDD has not been reported.
Keywords: Cat; intervertebral disc; neurology